Studi Pemnfaatan Lumpur, Abu Boiler, Dan Serat (Fiber) Kelapa Sawit Sebagai Kompos Menggunakan Variasi Effective Microorganisme (EM-4) - Gunadi Priyambada; Elvi Yenie; Ivnaini Andesgur (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
The process of palm oil mill wastewater treatment produced by-product as sludge. Sludge generated made a problem for environment and for industry when no handling and processing of the sludge. The purpose of this research is to reduce the pollution of palm oil mill wastewater by composting method with sludge, boiler ash and fiber (fiber) material of palm oil. Sludge mixed with boiler ash, fiber, and domestic wastethen added activator EM-4. Thisstudy used variety of activators EM-4  for 0,5%, 0,7%, 0,9% and control as comparator to optimize the composting process. The result showed that the compost with activator EM-4 for 0,7% likely matured faster because C/N ratio was suitable of SNI 19-7030-2004 and did not shows  significant differences. Compost matured in the 21th day  with result (C-org 27.22; Ratio of C/N  = 10.76;). Based on these results, palm oil sludge can be used as compost by using activators EM-4.  Keywords : activators EM-4, boiler ash, compost,  fiber, palm oil sludge